Working Politically: A story of Change about the contribution of resea rch evidence to the new Village Law in Indonesia - Pellini, Arnaldo; Angelina, Maesy; Purnawati, Endah (Austrialian Community Development, 2014)
On 18 December 2013, the Indonesian House of Representatives passed th e new Village Law, a vote that was the culmination of a journey that h ad started in 2007. This Story of Change takes the passing of the Vill age Law as its starting point and describes the relative influence tha t research-based evidence, produced by the Institute for Research and Empowerment (IRE), has had at critical junctions of the legislative pr ocess. This Story of Change concludes that good quality, research-base d evidence is necessary but not sufficient to influence policy-making processes. Researchers and research organisations need to think and wo rk politically to achieve their influencing goals and to adapt to chan ges in local circumstances.